2019
DOI: 10.1017/s0007114519002393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flaxseed oil on muscle protein loss and carbohydrate oxidation impairment in a pig model after lipopolysaccharide challenge

Abstract: Flaxseed oil is rich in α-linolenic acid (ALA), which is the metabolic precursor of EPA and DHA. The present study investigated the effect of flaxseed oil supplementation on lipopolysaccharide (LPS)-induced muscle atrophy and carbohydrate oxidation impairment in a piglet model. Twenty-four weaned pigs were used in a 2 × 2 factorial experiment including dietary treatment (5 % maize oil v. 5 % flaxseed oil) and LPS challenge (saline v. LPS). On day 21 of treatment, the pigs were injected intraperitoneally with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…11 We have found that the levels of pro-inflammatory cytokines in plasma and mRNA expression of genes related to inflammation and protein degradation in muscles increased in weaned pigs 4 h after LPS challenge. 12,13 Previous studies have reported that innate immune cells could be in diverse states with different degrees of pro-and anti-inflammatory phenotypes, 14,15 accompanied by varying consequences for host defense and inflammation. 16 Although LPS has been used for decades for the induction of some pro-inflammatory cytokines, the response and kinetics of inflammation varied extensively depending on the LPS timing.…”
Section: Introductionmentioning
confidence: 99%
“…11 We have found that the levels of pro-inflammatory cytokines in plasma and mRNA expression of genes related to inflammation and protein degradation in muscles increased in weaned pigs 4 h after LPS challenge. 12,13 Previous studies have reported that innate immune cells could be in diverse states with different degrees of pro-and anti-inflammatory phenotypes, 14,15 accompanied by varying consequences for host defense and inflammation. 16 Although LPS has been used for decades for the induction of some pro-inflammatory cytokines, the response and kinetics of inflammation varied extensively depending on the LPS timing.…”
Section: Introductionmentioning
confidence: 99%
“…And the genes of D5D (Δ5-desaturase) and D6D (Δ6-desaturase) expression of piglets are affected ( 52 ). Flaxseed oil may have a positive effect on alleviating muscle protein loss and carbohydrate oxidation impairment induced by LPS challenge through regulation of TLR4/NOD and Akt/FOXO signaling pathways ( 53 ). Murtilla or murta ( Ugni molinae Turcz), a plant of the Myrtaceae family, is rich in phenolic components.…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%
“…The mature IL-1 β and IL-18 molecules are secreted through cell membrane pores constituted by GSDMD proteins and exacerbate the inflammatory response to pyroptosis [ 33 35 ]. In contrast, n-3 PUFAs can inhibit inflammatory signaling pathways by suppressing TLR-induced signaling [ 36 , 37 ] and suppress NLRP3 inflammasome activity, resulting in anti-inflammatory effects and the inhibition of pyroptosis development [ 38 ]. Few studies have examined the effects of MUFAs and n-6 PUFAs on TLR4 signaling and pyroptosis, and their results have been mixed.…”
Section: Introductionmentioning
confidence: 99%